The Game for Three: Salmonella–Host–Microbiota Interaction Models - Grzymajlo, Krzysztof (Frontiers in Microbiology, 2022)
Colonization of the gastrointestinal tract by enteric pathogens occurs in a context strongly determined by host-specific gut microbiota, which can significantly affect the infection outcome. Complex gameplay between trillions of microbes inhabiting the gastro-intestinal tract, the host, and the infecting pathogen defines a specific triangle of interaction; therefore, a complete infection model should consider all of these elements. Many different infection models have been developed to explain the complexity of these interactions. This review sheds light on current knowledge, along with the strengths and limitations of in vitro and in vivo models utilized in the study of Salmonella-host-microbiome interactions. These models range from the simplest experiment simulating environmental conditions using dedicated growth media to in vitro interaction with cell lines and 3-D organoid structure, and sophisticated “gut on a chip” systems in various animal models. Finally, the challenges facing this field of research and the important future directions are outlined.